2009
DOI: 10.1038/oby.2008.532
|View full text |Cite
|
Sign up to set email alerts
|

Independent Evolution of Heart Autonomic Function and Insulin Sensitivity During Weight Loss

Abstract: In order to investigate the improvement of insulin resistance and cardiac autonomic function along massive weight loss, 12 obese women were evaluated before, and 3 and 12 months after Roux‐en‐Y gastric bypass. The 12‐month values were compared to those of BMI‐matched controls. Insulin sensitivity was assessed by euglycemic clamp and the cardiac autonomic function by the analysis of the Heart Rate Variability (HRV). After surgery, glucose uptake progressively increased from 4.3 ± 0.5 mg/kg lean body mass (LBM)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
3
20
1
2
Order By: Relevance
“…In fact, all these results show that the causes of impairment in cardiac autonomic modulation are still unclear, thus requiring further investigation on the correlation between autonomic dysfunctions and possible metabolic disorders; however this supposition was not addressed in the present study [29][30]. On the other hand, our study has shown that physical training can attenuate the cardiac autonomic modulation impairment in both obese and overweight women.…”
Section: Parameterscontrasting
confidence: 39%
“…In fact, all these results show that the causes of impairment in cardiac autonomic modulation are still unclear, thus requiring further investigation on the correlation between autonomic dysfunctions and possible metabolic disorders; however this supposition was not addressed in the present study [29][30]. On the other hand, our study has shown that physical training can attenuate the cardiac autonomic modulation impairment in both obese and overweight women.…”
Section: Parameterscontrasting
confidence: 39%
“…Weight loss induced by caloric restriction appears to exert favorable effects on ANS activity via enhancing vagal activity and/or reducing sympathetic modulation in overweight or obese otherwise healthy individuals (7)(8)(9)(10)(11)(12). However, the results across studies are inconsistent, and the mechanisms implicated in these effects are unclear.…”
mentioning
confidence: 74%
“…In glucose-tolerant obese subjects, chronic hyperinsulinemia was associated with persistent baroreflex downregulation and episodic (postprandial) sympathetic dominance, and reversal of these changes by weight loss suggested a causal role for insulin (13). However, in normoglycemic obese women, weight loss after Roux-en-Y gastric bypass independently improved HRV and glucose uptake (10). Caloric restriction in overweight individuals over 6 months was accompanied by improved vagal activity and reduced sympathetic activity only when combined with exercise despite weight loss comparable to caloric restriction only (11).…”
mentioning
confidence: 97%
“…Por otra parte, la RI se define como una disminución a la respuesta fisiológica a la insulina por parte de los tejidos, particularmente a nivel del tejido muscular y adiposo 27 . Si se considera a la obesidad y el sobrepeso como la característica principal de la muestra del presente estudio, se presume que existe un estilo de vida poco saludable, caracterizado por el desbalance entre el gasto y el consumo calóri-co, constituyendo una serie de factores de riesgo para el desarrollo de anormalidades metabólicas, disautonomía y síndrome metabólico 7,28 . Sumado a esto, existen estudios epidemioló-gicos que han demostrado que la obesidad y RI, se asocian con un incremento de la FC de reposo debido a un estímulo adrenérgico 20 .…”
Section: Discussionunclassified